PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN Terdaftar di Bursa Efek Indonesia Tahun 2018 - 2020 - Esther Liana Rini Andriyani; Endang Purwanti; Joko Pramono (ECONBANK: Journal of Economics and Banking, 2022)
This study aims to determine the effect of Good Corporate Governance (proxied by the board of commissioners, board of directors, audit committee, and institutional ownership) on the profitability of banking companies (Return on Equity (ROE)). This type of research is explanatory research with a quantitative approach. The population in this study are banking companies listed on the Indonesia Stock Exchange in 2018-2020. The sample selection is by purposive sampling. Data analysis used classical assumption test, multiple linear regression analysis, hypothesis test and the coefficient of determination. The results of the study show that (1) the Board of Commissioners has no significant effect on the profitability of banking companies. (2) The Board of Directors has a significant effect on the profitability of banking companies. (3) The Audit Committee has no significant effect on the profitability of banking companies. (4) Institutional Ownership has no significant effect on the profitability of banking companies. While the results of the simultaneous f test show that the variables of the board of commissioners, board of directors, audit committee and institutional ownership have a simultaneous effect on the profitability of banking companies